A CONTRIBUTION TO THE STUDY OF THE FEMALE VOTE IN COSTA RICA - Carballo Murillo, Natalia (Revista de Ciencias Sociales, 2020)
This research seeks to contribute to the studies of the female vote in Costa Rica by analyzing the petitions of the Feminist League and other women, speeches that were pronounced from 1948 to 1952 in newspapers and in the records of the Legislative Assembly. It was observed that petitions emphasized women’s abilities and, in the approval discussions, their romantic, stereotypical and innocent image was validated. Once the vote is approved, women are ratified as decision-making subjects at the ballot box.